Potentiality of intercropping in managing Diamondback moth (Plutella xylostella) - SHARMA, KULDEEP; MAHLA, M K; RAMESH BABU, S; AHIR, K C; KUMAR, A; SINGH, BEERENDRA; CHEEMA, RUPINDER SINGH (The Indian Journal of Agricultural Sciences, 2022)
The present experiment was conducted at horticulture farm of Rajasthan College of Agriculture, Udaipur, Rajasthan, during two winter (rabi) seasons 2019–20 and 2020–21. The treatments include, cabbage + marigold, cabbage + onion, cabbage + garlic, cabbage + marigold + insecticides spray, cabbage + onion + insecticides spray, cabbage + garlic + insecticides spray, cabbage + insecticides spray and cabbage sole without insecticide spray as untreated control. The insecticidal treatments scheduled with two sprays, viz. first spray of chlorfenapyr 10% sc @200 g a.i./ ha and spinosad 45% sc @45 g a.i./ha. During both years, cabbage intercropped with marigold + insecticides spray proved to be the best treatment with the lowest mean DBM larval population (0.73 and 0.47 larvae/plant) and highest benefit-cost ratio (6.69 and 6.88). Additionally, the intercrops treatments, viz. cabbage + marigold, cabbage + onion and cabbage + garlic also significantly reduced the number of DBM larvae per plant as compared to the untreated sole cabbage. The different intercrops combinations evaluated had a positive effect on the cabbage crop in reducing the pest and can be taken to manage DBM in a sustainable way.